Employee Well-being in Retail Operations: Conceptual Model and Theoretical Propositions for Organizational Performance - Wawat Hermawati (Journal Of Resource Management, Economics And Business, 2025)
Purpose: This conceptual study aims to develop a theoretical model explaining how employee well-being affects organizational performance through the Job Demands-Resources (JD-R) model, particularly in the retail sector, characterized by long working hours, intensive customer interactions, and high-performance pressure Research Methodology: A narrative literature review was conducted on 38 studies related to well-being, job stress, and employee performance in the retail sector (2010–2024). The study integrates the concept of well-being with the JD-R theory to construct a conceptual framework. Results: The findings show that job demands, such as workload and role conflict, negatively impact well-being, while job resources, such as organizational support, supervisor support, and work-life balance, serve as buffers that protect employee well-being. Good employee well-being leads to improved individual and organizational performance. Limitations: This study is conceptual, and further empirical validation is needed. The focus is primarily on operational employees, with limited exploration of middle management or other retail sectors Contribution: The study contributes by proposing an integrative model that positions well-being as a strategic foundation in modern retail management. Practical implications include the need for human-centered HR policies and the regular measurement of employee well-being.